Effects of Sensory Feedback and Collider Size on Reach-to-Grasp Coordination in Haptic-Free Virtual Reality - Furmanek, Mariusz P.; Mangalam, Madhur; Lockwood, Kyle; Smith, Andrea; Yarossi, Mathew; Tunik, Eugene (Frontiers in Virtual Reality, 2021)
Technological advancements and increased access have prompted the adoption of head-mounted display-based virtual reality for neuroscientific research, manual skill training, and neurological rehabilitation. Applications that focus on manual interaction within the virtual environment, especially haptic-free virtual reality, critically depend on virtual hand-object collision detection. Knowledge about how multisensory integration related to hand-object collisions affect perception-action dynamics and reach-to-grasp coordination is needed to enhance the immersiveness of interactive VR. Here we explored whether, and to what extent, sensory substitution for haptic feedback of hand-object collision (visual, audio, or audiovisual) and collider size (size of spherical pointers representing the fingertips) influence reach-to-grasp kinematics. In Study 1, visual, auditory, or combined feedback indicated the successful grasp of the virtual objects. In Study 2, participants reached and grasped virtual objects using spherical colliders of different diameters. Our data indicate that collider size but not sensory feedback significantly affected the kinematics of grasping. Larger colliders led to a smaller size-normalized peak aperture suggesting a possible influence of spherical collider size on the perception of virtual object size and motor planning of reach-to-grasp. Critically, reach-grasp spatiotemporal coordination patterns were robust to manipulations of sensory modality for haptic sensory substitution and spherical collider size. These results have important implications for research, commercial, industrial, and clinical applications of virtual reality.